Influence analysis of instructional models and motor skills towards student achievement on sprint - Anggil Jufinda; Ade Irawan (Global Econedu, 2019)
According to an initial observation conducted in SMPN 4 Kerinci, there were at least three biggest problems with the school: 1) absence of varied instructional models 2) lack of the students’ interest in learning sprint, 3) the students’ low achievements in sprint. This study aimed to analyse the influence of instructional models and motor skills towards seventh grade-student achievement on sprint at SMPN 4 Kerinci. This study employed experimental methods, with treatment by level 2x2 design. Sample of this study is 64 students who involved within two treatment groups. Results of this study showed that group of students who were taught using creative play instructional model comprehensively performed better in sprint compared to the students taught using cooperative instructional model. There was an interaction between instructional models and motor skills towards student achievement on sprint.